Borassus aethiopum activated carbon prepared for nitrate ions removal. (2nd January 2022) - Koné, Horo; Assémian, Alain Stéphane; Tiho, Tagouèlbè; Adouby, Kopoin; Yao, Kouassi Benjamin; Drogui, Patrick
Abstract : This work aims to study nitrate ions removal using Borassus aethiopum activated carbon (BA-AC) in a synthetic medium. BA-AC was prepared through artisanal method in order to provide a low-cost activated carbon. Physico-chemical characterization of BA-AC has shown a high-specific surface area (1431 m 2 /g). Analysis of surface morphology by scanning electron microscopy, mean pore diameter (2.76 nm) and adsorption/desorption isotherm resulted in the mesoporous adsorbent. The existence of functional groups (C = O; C–H; C–OH) was highlighted by Fourier Transform Infrared spectroscopy. A percentage of 60.56% for nitrate ions at pH 4 was reached. Pseudo-second-order kinetic and Langmuir isotherm were the most suitable models to describe adsorption process. The thermodynamic study revealed that adsorption mechanism occurs spontaneously (ΔG° < 0). Enthalpy (ΔH° = 1.89 kJ.mol −1 ) and entropy (ΔS° = 19.03 J.mol −1 K −1 ) values indicate an endothermic process with an increase of disorder at the solid–liquid interface.